Priests of Christ: Unity Fraternity and Spirituality - Areeplackal, Joseph (Journal of Dharma, 1999)
Jose Tharayil, Priests of Christ: Unity Fraternity and Spirituality. Alwaye: Pontifical Institute Publications PP• xv + 215, 1995, Rs. 200; 19.95.